Pelet Ikan Berbahan Dasar Limbah Kulit Pisang Cavendish (Musa Acuminata Cavendish Subgroup) dengan Penambahan Fermentasi Daun Pepaya (Carica Papaya) - Frengki Prabowo Saputro Wijayanto; Elnino Profetika Zarathrustra; Widayoko, Agus (Jurnal Integrasi Sains dan Quran, 2022)
Fish feed is one of the factors that crucial in the growth process of fish. One of the fish-feed is the pellets. The purpose of this study was to utilize Cavendish Banana peel waste (Musa Acuminata Cavendish Subgroup) as fish pellets with the addition of papaya leaves through a fermentation process to fulfill fish nutrition. This type of research is descriptive research with a qualitative approach. The focus of the description is on the process of making pellet. It is hoped that in the future, this product can be the basis for further research related to fish pellets.